Experimental study on mechanical characteristics of nut rupturing under impact loading - Chengmao, Cao; Si, Sun; Ran, Ding; Bing, Li; Shuo, Wang (International Journal of Agricultural and Biological Engineering, 2017)
The parameters of energy and power for nut rupturing play a key role in the design of shell-breaking equipment. However, currently, there is no scientifically accurate measuring method for these parameters. A mechanical nut testbed was developed to accurately measure the force, energy, and power and observe the generating process of nutshell cracking and breaking to reveal the shell-breaking mechanism. The system was tested with pecans and the results show that the testbed can effectively realize the determination of nuts performance and data acquisition and analysis. The methods and data can provide a theoretical guidance for the design and optimization of shell-breaking equipment and decrease kernel-breaking rate.Keywords: nutshell breaking, moisture content, shell-breaking energy, shell-breaking power, shell-breaking mechanismDOI: 10.3965/j.ijabe.20171001.2331Citation: Cao C M, Sun S, Ding R, Li B, Wang S. Experimental study on mechanical characteristics of nut rupturing under impact loading. Int J Agric & Biol Eng, 2017; 10(1): 53–60.